Clinical utility of anterior segment swept-source optical coherence tomography in glaucoma - Angmo, Dewang (Oman J Ophthalmol, 2016)
Optical coherence tomography (OCT), a noninvasive imaging modality that uses low-coherence light to obtain a high-resolution cross-section of biological structures, has evolved dramatically over the years. The Swept-source OCT (SS-OCT) makes use of a single detector with a rapidly tunable laser as a light source. The Casia SS-1000 OCT is a Fourier-domain, SS-OCT designed specifically for imaging the anterior segment. This system achieves high resolution imaging of 10΅m (Axial) and 30΅m (Transverse) and high speed scanning of 30,000 A-scans per second. With a substantial improvement in scan speed, the anterior chamber angles can be imaged 360 degrees in 128 cross sections (each with 512 A-scans) in about 2.4 seconds. We summarize the clinical applications of anterior segment SS-OCT in Glaucoma. Literature search: We searched PubMed and included Medline using the phrases anterior segment optical coherence tomography in ophthalmology, swept-source OCT, use of AS-OCT in glaucoma, use of swept-source AS-OCT in glaucoma, quantitative assessment of angle, filtering bleb in AS-OCT, comparison of AS-OCT with gonioscopy and comparison of AS-OCT with UBM. Search was made for articles dating 1990 to August 2015.